Standardization of Chargers for Portable Electronic Devices in the Saudi Market - Aldhubaib, Hani; Abu-Hashem, Muhannad A.; Shambour, Mohd Khaled (Journal of King Abdulaziz University: Engineering Sciences, 2023)
In recent years, portable devices such as mobile phones, tablets, digital cameras, headphones, and portable speakers have been used more commonly. These devices usually come with a particular type of charger that may or may not be suitable for use with other devices. The incompatibility issue of chargers has garnered much attention worldwide in the last few years, including in Saudi Arabia. The main points of investigation are the environmental, economic, and social impacts of having many types of chargers for portable electronic devices. Due to the massive size of the electronic market in Saudi Arabia, this paper aims to survey consumers’ opinions about the current situation of chargers and assess the potential impact of standardizing chargers in the Saudi market. The descriptive analytics approach is used in this study through an electronic questionnaire. The study received 1,527 responses from 13 provinces within Saudi Arabia. The results demonstrate serious challenges associated with electronic device chargers and the significant need to standardize them. The environmental, social, and economic benefits of this standardization are outlined. The findings of this paper recommend that policymakers in Saudi Arabia embrace the standardization of chargers for all portable electronic devices.